BOUNDED RATIONALITY, INCREMENTALISME, DAN POLITIK DALAM PEMBUATAN KEBIJAKAN: ANALISIS PADA PENGGUNAAN DATA KEMISKINAN DI INDONESIA, 1998-2025 - Adfin Rochmad Baidhowah; Agus Toyib (Jurnal Kebijakan Pemerintahan, 2026)
Abstract Although poverty data plays a central role in the formulation of social protection policies in Indonesia, most previous studies have focused on the technical aspects of measurement, statistical accuracy, and the effectiveness of program targeting. The literature has relatively little exploration of poverty data as a policy object undergoing long-term institutional change and influenced by the state's bounded rationality, patterns of policy incrementalism, and political pressures in the post-Reformation democratic context. This gap is increasingly relevant given the repeated changes in data regimes, from BPS macro data, ad hoc poor household data collection, the Integrated Database, the Integrated Social Welfare Data, to the launch of the National Single Social and Economic Data in 2025. This study aims to analyze the dynamics of Indonesia's national poverty data policy from the 1998 Reformation to 2025, emphasizing three main dimensions: bounded rationality in state decision-making, patterns of incremental policy change, and increasing political pressure and demands for data accuracy in the distribution of social assistance. The method used was archival research, which systematically examined policy documents, laws and regulations, official government reports, publications from statistical agencies, and institutional archives related to poverty alleviation and social protection. The analysis was conducted qualitatively and historically to identify patterns of continuity and change in data policy. The results indicate that poverty data policy developed through a fragmented, incremental process due to bounded rationality and institutional sectoral egos. The DTSEN represents a corrective effort by the state to shift toward a single data governance system, while simultaneously acknowledging the limitations of previous policy approaches. Keywords: bounded rationality; policy incrementalism; politics of data; poverty policy.